The developing of motivation for a healthy lifestyle for pupils [Articol] - Blîndul, Mihaela (CEP USM, 2023)
The article addresses the dimension of motivation for developing healthy lifestyles in students. Motivation is formed by a combination of different factors, including: needs and desires, goals, rewards and punishments, emotions, personal values, social influence. Intrinsic motivation is the basis for the formation and development of a healthy lifestyle and the achievement of desired, long-term results. Thus, motivation plays a key role in maintaining interest in learning and exploration by managing and regulating effort, even when obstacles arise. This requires strong awareness, willpower and perseverance. Therefore an important aspect in the context of adopting a health-focused lifestyle is the formation and development of motivation, as an essential foundation for achieving goals.

În articol este abordată dimensiunea motivației pentru dezvolarea modului de viață sănătos la elevi. Motivația se formează printr-o combinație de diverși factori, printre care: nevoile și dorințele, obiectivele, recompensele și pedepsele, emoțiile, valorile personale, influența socială. La baza formării, dezvoltării unui stil de viață sănătos și dobândirea rezultatelor dorite și pe termen lung stă motivația intrinsecă. Astfel, motivația joacă un rol esențial în menținerea interesului învățării și explorării prin gestionarea și reglarea efortului depus, chiar și atunci când apar obstacole. Acest lucru necesită o puternică conștientizare, voință și perseverență. De aceea un aspect important în contextul adoptării unui stil de viață axat pe sănătate este formarea și dezvoltarea motivației, fiind un fundament esențial la atingerea scopurilor.
FORMAREA MOTIVAȚIEI PENTRU UN MOD DE VIAȚĂ SĂNĂTOS LA ELEVI
Keywords: healthy lifestyle; motivation; motivational adjustment; automotivation; intrinsic motivation; extrinsic motivation; mod de viață sănătos; motivație; reglarea motivațională; automotivare; motivație intrinsecă; motivație extrinsecă